Laajan kielimallin hyödyntäminen kuluttajaneuvonnan tapausten tiivistelmien tuottamisessa - Suovuori, Johan Kaarlo August (2024)
Large language models, such as the GPT language models developed by OpenAI, have recently become widely known and popular, especially due to the success of ChatGPT. The popularity is justified, as these language models have become so advanced that they can be successfully utilized in various demanding use cases. The purpose of this study is to determine whether GPT-3.5 could produce high-quality summaries of different cases submitted to the Finnish Competition and Consumer Authority's consumer advisory services. Annually, the authority receives about 65,000 such cases, so producing summaries for all of them manually would require an enormous amount of work. However, summaries would be useful for internal use and could have other applications beyond internal use, such as responding to media inquiries. The research was conducted as a design science study, with a primary focus on prompt engineering for the language model. In addition to prompt engineering, the study addresses the theory of language models, evaluation of the produced summaries, cost, technical implementation, risks, and operational impacts. The use of the language model for summary creation mostly met the set goals, but there is still room for improvement. Nevertheless, the study laid a good foundation for enhancing the FCCA’s AI capabilities for other use cases in the future.